FAKTOR-FAKTOR KESULITAN BELAJAR PESERTA DIDIK PADA MATA PELAJARAN GEOGRAFI SMA ISLAM BAWARI PONTIANAK - Nur Hafiza; Sulistyarini Sulistyarini; Diah Trismi Harjanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThe purpose of this research is to determine the factors that cause of the difficulties in learning Geography subject to 11th grade students of SMA Islam Bawari Pontianak. The type of this research is using descriptive with the qualitative method. The data sources of this research were the Geography subject teacher of SMA Islam Bawari Pontianak, and 15 of 11th grade students of SMA Islam Bawari Pontianak. Data collection techniques in this research were observations, interviews, and documentations. The data collection tools used were interview guides and documentation tools. The results of this research point out that 1) The internal factors that cause the difficulties in learning are including intelligence, atttention, interest, the self-confidence, and the habits of study. 2) The external factors that cause the difficulties in learning are including facilities and infrastructure factors and the environment around students. 3) The effort to resolve the difficulties in learning that carried out by teacher are including providing tutoring, implementing remedial programs, providing motivation, and giving assignmet which the purpose is to make the students learn more independently.Keywords: Difficulties in Learning, Geography Subject, Students